2017
DOI: 10.1086/689408
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Rate of Diploid and Triploid Edible FrogPelophylax esculentusCorrelates Inversely with Cell Size in Tadpoles but Not in Frogs

Abstract: In multicellular organisms, cell size may have crucial consequences for basic parameters, such as body size and whole-body metabolic rate (MR). The hypothesis predicts that animals composed of smaller cells (a higher membrane surface-to-cell volume ratio) should have a higher mass-specific MR because a large part of their energy is used to maintain cell membranes and ionic gradients. In this article, we investigated the link between cell size and MR in diploid and triploid tadpoles and froglets of the hybridog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 53 publications
1
20
2
Order By: Relevance
“…Small cells (and organisms containing them) tend to have higher mass-specific metabolic rates than large cells (and organisms containing them) [26,[69][70][71][72][73][74][75][76][77]. Therefore, like the MTE, cell-size theory predicts that changing temperature should affect the elevation of metabolic scaling relationships, but not their slopes (but see Section 3.2.2), which again is contradicted by the results described in this study.…”
Section: Implications Of Results For Theorycontrasting
confidence: 82%
“…Small cells (and organisms containing them) tend to have higher mass-specific metabolic rates than large cells (and organisms containing them) [26,[69][70][71][72][73][74][75][76][77]. Therefore, like the MTE, cell-size theory predicts that changing temperature should affect the elevation of metabolic scaling relationships, but not their slopes (but see Section 3.2.2), which again is contradicted by the results described in this study.…”
Section: Implications Of Results For Theorycontrasting
confidence: 82%
“…Since that time, many investigators have discussed the cell-size model, including providing additional theoretical formulations, conceptual justifications, and empirical tests [19,20,56,97,105,106,130,[143][144][145][146][147][148]. However, so far the model has received mixed empirical support [19,20,97,105,106,[139][140][141][142][143]145,[149][150][151][152][153][154][155].…”
Section: Surface-area Modelsmentioning
confidence: 99%
“…In any case, tests of the identical predictions of the SA and RT versions of the cell-size model have produced mixed support (see Section 2.2.1). Most support comes from scaling analyses at the intraspecific (ontogenetic) level (the focal level of the RT model [130]; but see [152,155]), whereas support at the interspecific level is weaker. For example, although cell-size models correctly predict the hypometric (negatively allometric) scaling (slope~0.75) among species of insects [145], they do not for mammals.…”
Section: Resource-transport Modelsmentioning
confidence: 99%
“…This suggests that maintaining a specific cell size may be more beneficial (or at least easier) than to generate large organisms by increasing cell size. More recently, comparisons of diploid and triploid animals has revealed that especially in aquatic environments triploid animals tend to have a reduced metabolic rate, despite maintaining same organismal size [60], suggesting a potential fitness disadvantage for abnormally large cell size. These animals can be fully polyploid or may contain polyploid cells in otherwise normal diploid tissue.…”
Section: Polyploidy In Cells and Animals Reduces Fitness But May Imprmentioning
confidence: 99%